2017
DOI: 10.1097/tp.0000000000001377
|View full text |Cite
|
Sign up to set email alerts
|

Has the Department of Veterans Affairs Found a Way to Avoid Racial Disparities in the Evaluation Process for Kidney Transplantation?

Abstract: Background Minority groups are affected by significant disparities in kidney transplantation (KT) in Veterans Affairs (VA) and non-VA transplant centers. But, prior VA studies have been limited to retrospective, secondary database analyses that focused on multiple stages of the KT process simultaneously. Our goal was to determine whether disparities during the evaluation period for KT exist in the VA as has been found in non-VA settings. Methods We conducted a multi-center longitudinal cohort study of 602 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…Some studies have shown reduced racial disparity in health outcomes in the VHA, which does not have some of the barriers to subspecialty care that are prevalent elsewhere in the United States and that may particularly disadvantage minorities. 22,23 Kovesdy et al contrasted outcomes for a large cohort of veterans without CKD who received care in the VHA versus the general population. Black veterans had 24% lower all-cause mortality, whereas black patients in the general population experienced a 42% higher adjusted mortality versus white patients.…”
mentioning
confidence: 99%
“…Some studies have shown reduced racial disparity in health outcomes in the VHA, which does not have some of the barriers to subspecialty care that are prevalent elsewhere in the United States and that may particularly disadvantage minorities. 22,23 Kovesdy et al contrasted outcomes for a large cohort of veterans without CKD who received care in the VHA versus the general population. Black veterans had 24% lower all-cause mortality, whereas black patients in the general population experienced a 42% higher adjusted mortality versus white patients.…”
mentioning
confidence: 99%
“…Among the selected patients who were evaluated at VA transplant centers from the study above, 30% were not listed. 17 Once listed, living donor transplantation is the best option for all kidney transplant candidates, and our data show that the rate of living donation was particularly low in the VA transplant population compared with privately insured patients. In the study above, 41% of surveyed patients evaluated at VA transplant centers reported having a living donor candidate available.…”
Section: Discussionmentioning
confidence: 76%
“…16 A recent analysis looked at various factors related to the time from evaluation at a VA transplant center to successful listing. 17 That study did not account for the barriers and delays that may occur before evaluation at the transplant center. VA transplant centers may turn a patient down sight-unseen or request additional testing that may delay evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors including age, race, socioeconomic status and medical comorbidities affect KT evaluation and wait‐listing . Racial minorities including African Americans, Hispanics and Native Americans repeatedly have been shown to have less access to renal transplantation, and whether cognitive impairment plays a role in the lower probability of wait‐listing and KT in these populations has never been investigated.…”
Section: Introductionmentioning
confidence: 99%